TAXPAYER COMPLIANCE WITH TAX COLLECTION IN INDONESIA: ANALYSIS OF FACTORS AND IMPACT - Silva, Julio de Araujo da; Usfunan, Yohanes; Yasa, Putu Gede Arya Sumerta; Astariyani, Ni Luh Gede; Bagiastra, I Nyoman (Veredas do Direito, 2026)
Taxes are mandatory contributions from the public to the state treasury as regulated by law, so that their collection is compulsory and does not provide direct compensation to the payer. Meanwhile, taxpayer compliance is the action of taxpayers in fulfilling their tax obligations as regulated by law and following the regulations that apply in the country. The purpose of this scientific article is to determine the effect of taxpayer compliance on tax collection in Indonesia. This study uses a juridical-normative method with primary and secondary data sources. The analysis is conducted descriptively and qualitatively through theme grouping, data classification, and interpretation of legal meanings in a social context to obtain a comprehensive understanding of the issues under review. The results of the study show that tax awareness, tax knowledge, the quality of fiscal services, tax morality, and the application of sanctions have a significant effect on the level of taxpayer compliance. In addition, a high level of compliance can increase the efficiency of tax collection and optimize state revenue.